IDENTIFICATION OF SALT DEVELOPMENT PROBLEM : A PRELIMINARY ON UNDERSTANDING LOCAL SALT PROBLEM IN INDONESIA - Iffan Maflahah; Budisantoso Wirjodirdjo; Putu Dana Karningsih (AGROINTEK, 2020)
Salt is a strategic commodity that needs to be maintained. The salt problem has not resolved, so it is necessary to find the right solution for salt development. The study was carried out in Sampang Regency as a salt-producing area which was proposed for salt approval and formulated a policy for salt development. The research method used is the DPSIR method (Driving Power /; Pressure; State; Impact; Response). The main problems with developing salt are the impartiality of local salt prices, the supply chain system, changes in pond function, climate uncertainty, and inadequate infrastructure. Efforts must be made to develop salt are the modernization of the production process, controlled of salt price regulations, market search, improvement of human resources and structuring of supporting facilities for salt production should be carried out.